PRODUCTIVITY, EGG QUALITY, AND EGG COMPOSITION OF QUAIL SUPPLEMENTED WITH CASSAVA LEAF PASTE - La Jumadin (Polish Journal of Natural Sciences, 2023)
Cassava leaf paste contains macro, micro, and bioactive mineral nutrients that improve physiological performance. The study aimed to evaluate the effect of adding cassava leaf paste on the productivity and quality of quail eggs. The parameters measured were performance, egg quality, and quail egg composition. The results showed that the application of cassava leaf paste increased quail body weight gain. The average quail eggshell that received cassava leaf paste was thicker than the control group. The percentage of quail egg whites and egg yolks that received cassava leaf paste treatment was higher than the control. This study concluded that quail treated with cassava leaf paste resulted in higher quail performance such as body weight gain and egg mass. Giving cassava leaf paste causes the quail to be healthier by producing a higher egg composition such as the percentage of egg whites and yolks and thicker eggshells.